Ca. Nitrososphaera and Bradyrhizobium are inversely correlated and related to agricultural practices in long-term field experiments - Zhalnina, Kateryna; de Quadros, Patricia D.; Gano, Kelsey A.; Davis-Richardson, Austin; Fagen, Jennie R.; Brown, Christopher T.; Giongo, Adriana; Drew, Jennifer C.; Sayavedra-Soto, Luis A.; Arp, Dan J.; Camargo, Flavio A.; Daroub, Samira H.; et al. (Frontiers in Microbiology, 2013)
Agricultural land management, such as fertilization, liming, and tillage affects soil properties, including pH, organic matter content, nitrification rates, and the microbial community. Three different study sites were used to identify microorganisms that correlate with agricultural land use and to determine which factors regulate the relative abundance of the microbial signatures of the agricultural land-use. The three sites included in this study are the Broadbalk Experiment at Rothamsted Research, UK, the Everglades Agricultural Area, Florida, USA and the Kellogg Biological Station, Michigan, USA. The effects of agricultural management on the abundance and diversity of bacteria and archaea were determined using high throughput, barcoded 16S rRNA sequencing. In addition, the relative abundance of these organisms was correlated with soil features. Two groups of microorganisms involved in nitrogen cycle were highly correlated with land use at all three sites. The ammonia oxidizing-archaea, dominated by Ca. Nitrososphaera, were positively correlated with agriculture while a ubiquitous group of soil bacteria closely related to the diazotrophic symbiont, Bradyrhizobium, was negatively correlated with agricultural management. Analysis of successional plots showed that the abundance of ammonia oxidizing-archaea declined and the abundance of bradyrhizobia increased with time away from agriculture. This observation suggests that the effect of agriculture on the relative abundance of these genera is reversible. Soil pH and NH3 concentrations were positively correlated with archaeal abundance but negatively correlated with the abundance of Bradyrhizobium. The high correlations of Ca. Nitrososphaera and Bradyrhizobium abundances with agricultural management at three long-term experiments with different edaphoclimatic conditions allowed us to suggest these two genera as signature microorganisms for agricultural land use.